(untitled) - Celce-Murcia, Marianne (Cambridge, U.K., 1996)
This course includes an overview of current theory and practice.The paperback edition offers current and prospective teachers of English a comprehensive treatment of pronunciation pedagogy, drawing on current theory and practice. The text provides an overview of teaching issues from the perspective of different methodologies and second language acquisition research. It has a thorough grounding in the sound system of North American English, and contains insights into how this sound system intersects with listening, morphology, and spelling. It also contains diagnostic tools, assessment measures, and suggestions for syllabus design. Discussion questions encourage readers to draw on their personal language learning/teaching experiences as they assimilate the contents of each chapter. Follow-up exercises guide teachers in developing a range of classroom activities within a communicative framework.
Ngữ âm thực hành cơ bản
Keywords: English language,English language; Pronunciation,Study and teaching,Study and teaching,Foreign speakers